Czy możliwa jest wolność bez wolnej woli? (IS FREEDOM WITHOUT FREE WILL POSSIBLE?) - Przemysław Gut (Analiza i Egzystencja, 2008)
The main aim of this presents paper is to critically explore the view according to which an understanding and grasping of freedom is possible in the absence of free will. In the first part the author puts forward crucial reasons on which the tendency to postulate freedom of man without free will is based. In the second part the links existing between notions of freedom and knowledge are considered. The third part of this paper deals with the difficulties that the theory of freedom without free will faces in confronted with.